Sustainable Water Development in Iraq and Its Management Weaknesses (مجلة دراسات إقلیمیة, 2026)
Research Idea: This research examines sustainable water development and weaknesses in water management in Iraq. Achieving sustainability requires protecting natural water resources, including river water, groundwater, lake water, and rainwater harvested through dams. Reducing water losses and improving water-use efficiency are essential for lowering water stress and easing pressure on Iraq’s renewable water resources.Objective: The research aims to analyze the state of sustainable water development in Iraq during the period 1990–2023, examine water resources and their uses, assess water stress levels, and identify the major challenges and risks associated with weak water management. It also highlights the seriousness of the water crisis and its implications for food and national security.Methodology: The research adopts a descriptive and analytical approach supported by statistical tables, figures, and graphical data.Results: The findings reveal a sharp and continuous decline in the flows of the Tigris and Euphrates Rivers throughout the research period. They also show that the agricultural sector accounts for the largest share of freshwater consumption despite low water-use efficiency. In addition, modern water-saving techniques remain limited, including the use of cloud-seeding technologies that have become common in many countries.Conclusion: The research concludes that the continuation of current water-management practices without effective reforms poses a serious threat to environmental and economic sustainability in Iraq. It recommends adopting a comprehensive water strategy that includes improving irrigation techniques, developing wastewater-treatment systems, and strengthening regional partnerships to safeguard Iraq’s historical water rights and achieve sustainable water security.